Investigation of class 1 integrons and biofilm formation in multi-drug resistance uropathogenic Escherichia coli isolated from patients with urinary tract infection in Shohadaye Qom hospital, Iran - Ahmad Khorshidi; Nadia Mohammad Zadeh; Azad Khaledi; Gholam Abbas Moosavi; Ali Shakerimoghaddam; Azade Matinpur (International Archives of Health Sciences, 2022)
Aims: This study aimed to investigate class 1 integrons and biofilm formation in multi-drug resistance (MDR) Uropathogenic Escherichia coli (UPEC) isolated from patients with urinary tract infection (UTI). Materials and Methods: Three hundred and eighty positive cultures were collected from patients with UTI referred to Shohadaye Qom hospital from 2018 to 2019. Suitable tests were done to diagnose UPEC, and confirmed by usp gene polymerase chain reaction (PCR). Antibiotic susceptibility testing was performed using Kirby Bauer disk diffusion. Analysis of biofilm production was conducted using microtiter plate assay. Next, the presence of Class 1 integrons and dfr-17 gene was surveyed by PCR. Data analyzed using Chi-squared and Fisher's exact tests in SPSS software, P < 0.05 was considered statistically significant. Findings: In total, 166 isolates of UPEC were retrieved. Among them, 120 isolates were MDR. The highest resistance of MDRs was observed against ampicillin. Among MDRs, 71, 18, 15, and 16 isolates were negative, weak, moderate, and strong biofilm producers, respectively. Meanwhile, 47.5% of the isolates were positive for int-1 gene and 25.8% of the isolates were positive for dfr-17-gene cassette. Out of 57 int-1 positive MDRs, 15 isolates (26.3%) showed strong biofilm which indicated a significant correlation (P < 0.001). Furthermore, among 31 MDRs with the positive dfr-17, 8 isolates (25.8%) had strong biofilm which statistically was significant (P < 0.001). Conclusion: The present study reported a significant correlation between cassettes genes, Class 1 integrons, and biofilm formation with antibiotic resistance pattern. Hence, continuous screening for antibiotics resistance is vital for infection control and prevention.